Developing an islamic adab-based teacher leadership model to improve teacher performance in Islamic boarding schools - Dani Mohammad Ramdani (Universal Teaching and Learning Journal, 2025)
Purpose: This study aimed to improve teacher performance by improving the quality of teacher leadership. Research methodology: This study applies the Borg and Gall development model, with teachers as subjects. The study aims to identify teachers’ needs for an Islamic manners-based leadership model, design and develop its prototype, evaluate its validity and practicality, and assess its effectiveness. Data from experts and practitioners were collected through observations, surveys, and assessment sheets and analyzed using quantitative and descriptive methods. Results: The study shows a high need for Islamic adab-based leadership. The prototype, which comprised structured steps and components, achieved high validity (3.66) and practicality (3.20). Its application significantly improved teacher performance, with normality > 0.05, t-test < 0.05, moderate N-Gain (0.60), and 58% effectiveness. Conclusion: The Islamic adab-based teacher leadership model effectively improves teacher performance, demonstrating high validity and practicality, and fostering competence and moral integrity in both teaching and mentoring roles. Limitations: The study’s limitations include its focus on one institution, a small sample size with short implementation, and reliance mainly on teacher perspectives without broad input from students or parents. Contribution: This study develops a validated Islamic adab-based leadership model that enhances teacher performance, upholds ethical standards, enriches faith-based education literature, and offers practical guidance for educators and policymakers.